2019
DOI: 10.1186/s12889-019-7875-x
|View full text |Cite
|
Sign up to set email alerts
|

Variations of health check attendance in later life: results from a British birth cohort study

Abstract: BackgroundOlder adults are advised to attend a number of preventive health checks to preserve health and identify risk factors for disease. Previous research has identified a number of health and social factors, labelled as predisposing, enabling and need factors, using Andersen’s Behavioural Model of Health Service Use, that are associated with health care utilisation. We aimed to assess associations between factors from childhood and adulthood, and health check attendance in later life in a British birth coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…Additionally one study included in this systematic review identified a trend towards lower uptake in smokers; an important risk factor for CVD that is also socially patterned (49, 50). Similar findings were also reported by Wilson and colleagues (51). These reasons for non-uptake of health checks, in combination with the inequalities identified in this study, indicate that methods to improve engagement with NHS health checks and preventative screening methods may reduce inequalities in cardiovascular outcomes.…”
Section: Results In Contextsupporting
confidence: 92%
“…Additionally one study included in this systematic review identified a trend towards lower uptake in smokers; an important risk factor for CVD that is also socially patterned (49, 50). Similar findings were also reported by Wilson and colleagues (51). These reasons for non-uptake of health checks, in combination with the inequalities identified in this study, indicate that methods to improve engagement with NHS health checks and preventative screening methods may reduce inequalities in cardiovascular outcomes.…”
Section: Results In Contextsupporting
confidence: 92%
“…and gambling addiction, only smoking had a significant impact on health checkup behavior in Japan. Smoking reduces the chance of accessing health checks, which corresponds with the findings of previous studies [ 8 , 58 , 59 ]. This is because participating in risky behaviors that individuals know are harmful, makes them reluctant to have check-ups.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was consistent with Korkeila et al [ 57 ], who showed that divorced and widowed persons were more hesitant toward positive health behavior. Hoebel et al [ 58 ] and Wilson et al [ 59 ] found that married individuals were more willing to participate in regular health checks. This can be attributed to greater attention to health symptoms and higher awareness of preventive measures among those living with a partner [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, women with lower socioeconomic statuses are less likely to avail cancer screening examinations, which cost ¥500−¥1,000 with municipal subsidies ( 33 ). Individuals with low socioeconomic statuses generally exhibit a higher risk of smoking, drinking, physical inactivity, poor nutrition, and not undergoing PHCs ( 32 , 34 , 35 ). Therefore, it is also vital that health promotion policies for PHCs target patients with T2DM with low socioeconomic statuses.…”
Section: Discussionmentioning
confidence: 99%